Os meios de produção da castanha-do-Brasil ( Bertholletia Excelsa Bonpl.) A experiência e os meios de vida dos cooperados da Covema em Manicoré-AM - Farias, Luiz Matheus Barreto (Brasil, 2023)
The present study evaluated the effects of the commercialization of Brazil nuts in cooperative members of the Cooperativa Verde de Manicoré (COVEMA), located in the region of the middle Madeira River, Amazonas, in terms of human, social, physical, financial and natural dimensions. The study methodology involved the application of semi-structured questionnaires, which seek to characterize the chest nut trees and analyze their perceptions about the effect of chestnut collection on their family and community life. Fieldwork was carried out in January and February 2017, when 30 people were interviewed. Respondents reported working with other non timber forest products such as açaí, copaíba, Seringa, sorva and tucumã. The sale of nuts contributes more positively to the population's livelihood in its physical and financial dimensions, due to the possibility of generating income that the activity can provide.